The Economic Behavior of Seaweed Farmers' Households in Pasikolaga Sub District Muna District - Nur Rahmawati; Rosmawaty Rosmawaty; La Ode Kasno Arif (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This study aims to determine the economic behavior of seaweed cultivator households in Kolese Village, Pasikolaga District, Muna Regency. This research was conducted in Kolese Village, Pasikolaga District, Muna Province. Household economics includes a discussion of household economic behavior regarding production, working hours, income, and household consumption expenditures. The survey subjects were 47 people, carried out by simple random sampling. zc The data analysis used is a quantitative descriptive analysis method. Based on the research results, the average income of seaweed cultivators is 1,608 kg/year. The time spent growing seaweed reached 4.81%, packing seaweed reached 25.42%, and drying time reached 3.53%. The average household income earned by farmers is IDR. 18,924,818. The average expenditure for food was IDR. 269,647, while for non-food expenditure, it was IDR. 767,987.